Kadar SGOT, SGPT, dan Bilirubin Total pada Pasien Tuberkulosis Paru - Titan Melina Putri; Widodo Widodo (Poltekkes Kemenkes Semarang, 2021)
Tuberculosis is an infectious infection caused by Mycobacterium tuberculosis. Anti Tuberculosis drug therapy given has side effects, one of which is hepatotoxicity.. The purpose of this study was to describe the levels of SGOT, SGPT, and total bilirubin in pulmonary tuberculosis patients based on the characteristics of gender and age. This type of research is descriptive observational with a case study approach. Data retrieval using purposive sampling of 120 patients was carried out by analyzing data on medical records. The results of the study in the intensive stage of treatment showed an increase in SGOT for 12 males and females an average of 71 U/L and 93 U/L. The SGPT of 12 men and 14 women averaged 86 U/L and 92 U/L. Total bilirubin in 10 men and 12 women averaged 1.58 mg/dl and 1.68 mg/dl, respectively. The increase in SGOT in 15 patients 26-45 years, 8 patients 46-65 years, and 2 patients >65 years averaged 79 U/L, 70 U/L, and 97 U/L. SGPT occurred in 15 patients 26-45 years, 8 patients 46-65 years, and 3 patients >65 years with mean levels of 82 U/L, 97 U/L, and 96 U/L. Total bilirubin occurred in 15 patients 26-45 years, 5 patients 46-65 years, and 2 patients >65 years with mean levels of 1.72 mg/dl, 1.38 mg/dl, and 1.57 mg/dl. , whereas in the advanced stage of treatment, all patients had normal levels of SGOT, SGPT, and total bilirubin with an average of 27 U/L, 29 U/L, and 0.41 mg/dl.